1997
DOI: 10.1037/0735-7028.28.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Defiance-based symptom prescription and psychological reactance: A critical evaluation.

Abstract: Symptom prescription is a commonly used clinical intervention that has been demonstrated to be effective for a wide range of client problems. The defiance-based form of symptom prescription has been frequently touted as an intervention of choice for clients who are characterized as resistant or reactant. This article critically examines case studies and controlled comparison studies that purport to address this hypothesized link between reactance and defiance-based symptom prescription. From this review, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
0
2
0
1
Order By: Relevance
“…While reactance was initially viewed to be situationally driven, later refinements suggested that it not only varies by situation, but also by individuals (Hunsley 1997). The 11-item scale asked respondents to indicate on a five-point Likert-type scale their agreement with each of the items (e.g., "Regulations trigger a sense of resistance in me;" "I become angry when my freedom of choice is restricted").…”
Section: Methodsmentioning
confidence: 99%
“…While reactance was initially viewed to be situationally driven, later refinements suggested that it not only varies by situation, but also by individuals (Hunsley 1997). The 11-item scale asked respondents to indicate on a five-point Likert-type scale their agreement with each of the items (e.g., "Regulations trigger a sense of resistance in me;" "I become angry when my freedom of choice is restricted").…”
Section: Methodsmentioning
confidence: 99%
“…These interventions are used after linear directives have failed and when the patient is noncompliant and symptoms are under voluntary control, although not all family psychologists are comfortable with paradoxical techniques (Sexton & Montgomery, 1994). A few of these techniques include the following: symptom prescription, symptom scheduling, symptom exaggeration, restraining, predicting relapses, prescribing relapses, prescribing no change, negative consequences of change, positioning, and making the symptom an ordeal (Duncan, 1989; Hunsley, 1997).…”
Section: Specialty Applied Proceduresmentioning
confidence: 99%
“…Shoham-Salomon et al, 1989. Εντούτοις, άλλες έρευνες υποστηρίζουν ότι το συγκεκριμένο μοντέλο δεν ισχύει στην πράξη (Dowd, Hughes, Brockbank, Halpain, Seibel, & Seibel, 1988. Hunsley, 1997.…”
Section: μελέτες για την αντιδραστικότητα σε σχέση με μεταβλητές της θεραπείαςunclassified